Association between sleep quality and mental illness among undergraduate students - Daud, Azlina; Othman, Hamidah; Hasmat, Nurul Ezam Asri (IIUM PRESS, 2023)
Introduction: Understanding the association between sleep quality and mental illness is indeed crucial for promoting the well-being of undergraduate students and addressing potential challenges before they become clinically significant. There is an association between sleep quality and mental health, and disruptions in one can affect the other. Thus, this study was conducted to examine the association between sleep quality and mental illness among undergraduate students. Methods: A cross-sectional study was conducted using a probability simple random sampling method among 347 International Islamic University Malaysia undergraduate students from February to April 2022. The data was collected using a self-administered questionnaire via Google Form. Two questionnaires were used in this study, Pittsburgh Sleep Quality Index for sleep quality and DASS-21 for mental health status. Results: The study findings showed that 176 individuals (50.7%) experience mild sleep difficulty, moderate levels of depression (23.3%), extremely severe levels of anxiety (13.3%), and moderate levels of stress (14.4%). Conclusion: These findings highlight the importance of promoting good sleep habits for the overall students’ well-being.